Segmentation of Total Cell Area in Brightfield Microscopy Images - Čepa, Martin (Methods and protocols, 2018)
Segmentation is one of the most important steps in microscopy image analysis. Unfortunately, most of the methods use fluorescence images for this task, which is not suitable for analysis that requires a knowledge of area occupied by cells and an experimental design that does not allow necessary labeling. In this protocol, we present a simple method, based on edge detection and morphological operations, that separates total area occupied by cells from the background using only brightfield channel image. The resulting segmented picture can be further used as a mask for fluorescence quantification and other analyses. The whole procedure is carried out in open source software Fiji.
Keywords: ImageJ; microscopy; cells; brightfield segmentation; image analysis; Fiji